2015
DOI: 10.1007/s10633-015-9489-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and electrophysiology findings in Slovene patients with Leber hereditary optic neuropathy

Abstract: In Leber hereditary optic neuropathy, a reduced N95 component of PERG and severely reduced VEP P100 may be present already in the acute stage of disease, before optic disc pallor appears, suggesting primary dysfunction of retinal ganglion cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
18
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 27 publications
4
18
1
Order By: Relevance
“…Similar PERG abnormalities, detected in our patients with LHON with 3460/ND1 mutation, were observed by others. 11,12,18,20,21 For the 14484/ND6 mutation, PERG abnormalities found in our present and previous study 12 are in agreement with those observed by others. 20,21 For the PERG abnormalities detected in patients with LHON with 14568/ND6 mutation, the present study represents a original finding because patients with LHON carrying this mutation have not been studied using an electrophysiologic approach.…”
Section: Retinal Ganglion Cell Functional Changes: Pattern Electroretsupporting
confidence: 93%
See 4 more Smart Citations
“…Similar PERG abnormalities, detected in our patients with LHON with 3460/ND1 mutation, were observed by others. 11,12,18,20,21 For the 14484/ND6 mutation, PERG abnormalities found in our present and previous study 12 are in agreement with those observed by others. 20,21 For the PERG abnormalities detected in patients with LHON with 14568/ND6 mutation, the present study represents a original finding because patients with LHON carrying this mutation have not been studied using an electrophysiologic approach.…”
Section: Retinal Ganglion Cell Functional Changes: Pattern Electroretsupporting
confidence: 93%
“…This is in contrast with Sharkawi et al, 18 who reported PERG improvement in only 1 case in which PERG was recorded by using similar visual stimuli. For the 14484/ ND6 mutation, we observed PERG improvement in 1 of 13 eyes (7.69%) in contrast to Jarc-Vidmar et al, 20 who reported no PERG changes in the only patient enrolled with this mutation after 30 months of follow-up. In the LHON-14568 patients, we observed a reduction in 60ʹ PERG A in 1 of 4 eyes, whereas by using 15ʹ checks, no eyes showed changes in PERG responses.…”
Section: Retinal Ganglion Cell Functional Changes: Pattern Electroretcontrasting
confidence: 92%
See 3 more Smart Citations